Implementasi Hak Dan Kewajiban Terhadap Pasien Dan Keluarga Dalam Pelayanan Yang Telah Diberikan (Studi Kasus Di RSUD KRMT WONGSONEGORO SEMARANG 2021) - Anisa Kurniasari (Pusat Riset dan Inovasi Nasional, 2022)
This study discusses the rights and obligations of patients and families in the services that have been provided. The results showed that the granting process was in accordance with the Constitution no. 36 of 2014 concerning Health Workers and the Regulation of the Minister of Health of the Republic of Indonesia Number 4 of 2018 concerning Hospital Obligations and Patient Obligations and other related regulations. There are several things that need to be improved, such as maximizing providing services to patients who have obligations that must be fulfilled, in order to achieve healing and as a balance of the rights they get, in essence the balance of rights and obligations is an achievement of a fairness of action, in terms of relationship between two parties (medical personnel and patients).